Answer:
The solution of the differential equation is
![B=5+25e^(-4t+4)](https://img.qammunity.org/2020/formulas/mathematics/college/itiyvia3hbvc52lbu8xsty3oyjnmc6oest.png)
Explanation:
The differential equation
is a first order separable ordinary differential equation (ODE). We know this because a separable first-order ODE has the form:
![y'(t)=g(t)\cdot h(y)](https://img.qammunity.org/2020/formulas/mathematics/college/adi6ka80fv8q4wcwu6e6tdsdjeu0fh0912.png)
where g(t) and h(y) are given functions.
We can rewrite our differential equation in the form of a first-order separable ODE in this way:
![(dB)/(dt)+4B=20\\(dB)/(dt)=20-4B\\(dB)/(dt)=4(5-B)\\(1)/(5-B)(dB)/(dt)=4](https://img.qammunity.org/2020/formulas/mathematics/college/kpqdubns0089apzuq3a0dhnzv5rowqdu2m.png)
Integrating both sides
![(1)/(5-B)(dB)/(dt)=4\\(1)/(5-B)\cdot dB=4\cdot dt\\\\\int\limits {(1)/(5-B)} \, dB=\int\limits {4} \, dt](https://img.qammunity.org/2020/formulas/mathematics/college/imreh8gonfelhg6jtmmcbw3mv0k3fdny34.png)
The integral of left-side is:
![\int\limits {(1)/(5-B)} \, dB\\\mathrm{Apply\:u-substitution:}\:u=5-B\\\int\limits {(1)/(5-B)} \, dB=\int\limits {(1)/(u)} \, dB\\\mathrm{du=-dB}\\-\int\limits {(1)/(u)} \,du\\\mathrm{Use\:the\:common\:integral}:\quad \int (1)/(u)du=\ln \left(\left|u\right|\right)\\-\int\limits {(1)/(u)} \,du =-\ln \left|u\right|\\\mathrm{Substitute\:back}\:u=5-B\\-\ln \left|5-B\right|\\\mathrm{Add\:a\:constant\:to\:the\:solution}\\-\ln \left|5-B\right|+C](https://img.qammunity.org/2020/formulas/mathematics/college/akrpj32zaldeuou0nw2ccsjbcyngfeowt6.png)
The integral of right-side is:
![\int\limits {4} \, dt = 4t + C](https://img.qammunity.org/2020/formulas/mathematics/college/8l4sqy1l3f9053ohd0fo7du2z8t0y7txp2.png)
We can join the constants, and this is the implicit general solution
![-\ln \left|5-B\right|+C=4t + C\\-\ln \left|5-B\right|=4t + D](https://img.qammunity.org/2020/formulas/mathematics/college/i8rwaeji7piwyttgwlxicsuyikn3v4uu3y.png)
If we want to find the explicit general solution of the differential equation
We isolate B
![-\ln \left|5-B\right|=4t + D\\\ln \left|5-B\right|=-4t+D\\\left|5-B\right|=e^(-4t+D)](https://img.qammunity.org/2020/formulas/mathematics/college/uwcq7ws25nuzqd8wncmn4ekwopl8bptqhk.png)
Recall the definition of |x|
![|x|=\left \{ {{x, \:if \>x\geq \>0 } \atop {-x, \:if \>x<\>0}} \right.](https://img.qammunity.org/2020/formulas/mathematics/college/28q5jy09rijai5vx2vzeci90p6p1mdr1u0.png)
So
![\left|5-B\right|=e^(-4t+D)\\5-B= \pm \:e^(-4t+D)\\B=5 \pm \:e^(-4t+D)\\B=5\pm \:e^(-4t)\cdot e^(D)\\B=5+Ae^(-4t)](https://img.qammunity.org/2020/formulas/mathematics/college/kz8rgl7akaxytvlmc5kanx1clx0vjup0eg.png)
where
![A=\pm e^(D)](https://img.qammunity.org/2020/formulas/mathematics/college/wgenql45b8hdszb10tiwdghd9ee78idy4n.png)
Now B(1) =30 implies
![B=5+Ae^(-4t)\\30=5+Ae^(-4)\\30-5=Ae^(-4)\\25e^(4)=A](https://img.qammunity.org/2020/formulas/mathematics/college/1d34ddeti2sxmqt0kdqnu3y8kpi67zjjfq.png)
And the solution is
![B=5+(25e^(4))e^(-4t)\\B=5+25e^(-4t+4)](https://img.qammunity.org/2020/formulas/mathematics/college/vulepx919acauetm5d4gno2lc8ved3yp2b.png)